Perfil epidemiológico de adultos/as mayores hospitalizados/as en el servicio de medicina interna del Hospital General Isidro Ayora de Loja - Jennifer Irene López Pinzón (2023)
The elderly present an increment of vulnerability to different pathologies due to their own natural evolution and socio-demographic characteristics. This research aims to analyse the epidemiological profile among elderly hospitalised in the internal medicine department of Isidro Ayora General Hospital in Loja during November and December 2021 to January and February 2022. This study was a mixed, descriptive, cross-sectional and nonexperimental approach, involving a simple random sample of 95 patients; a form was used to collect data, which were analysed by frequency and percentage statistics presented in tables. The data obtained demonstrate that 60% of the elderly are third age and 40% are fourth age; women constitute 51.6% and men 48.4%; regarding occupation, 51.6% do not work. The most frequent pathologies of the elderly are primary essential hypertension with 14.3%, non-insulin-dependent diabetes mellitus with 14.3%, anaemia with 8.1%, heart failure with 6.8%, chronic renal failure with 6.2%, hypothyroidism with 5.6%, gastric ulcers with 4.3%, urinary tract infection with 4.3%, non-insulin-dependent diabetes mellitus with 3.7% and bacterial pneumonia with 3.7%. Socio-demographic characteristics such as age, sex and occupation were related to the main pathologies of the elderly, indicating a predominance of primary essential hypertension and non-insulin-dependent diabetes mellitus. The data obtained from this research were socialised in the study area